Supramolecular fluorogenic peptide sensor array based on graphene oxide for the differential sensing of ebola virus. Issue 43 (23rd April 2020) - Fu, Meng-Qi; Wang, Xu-Chen; Dou, Wei-Tao; Chen, Guo-Rong; James, Tony D.; Zhou, Dong-Ming; He, Xiao-Peng
Abstract : Principal component analysis of a fluorescent supramolecular sensor array based on graphene oxide can be used to differentiate ebola virus from marburg virus and receptor-extensive vesicular stomatitis virus. Abstract : We report on a supramolecular sensor array using fluorogenic peptide probes and graphene oxide that can target glycoproteins on a viral caspid, facilitating the differentiation of ebola virus from marburg virus and receptor-extensive vesicular stomatitis virus using principal component analysis.